TIGIT limits immune pathology during viral infections - Michelle Schorer (Nature Portfolio, 2020)
TIGIT is a lymphocyte co-inhibitory receptor that can limit type 1 and cytotoxic T cell responses and maintain immunological tolerance. Here the authors show that TIGIT also limits immune pathology during LCMV or influenza infections in mice by driving IL-10 expression without negatively affecting the viral load.